Transient Immune Activation in BCG-Vaccinated Infant Rhesus Macaques Is Not Sufficient to Influence Oral Simian Immunodeficiency Virus Infection. (12th October 2019) - Wood, Matthew P; Wood, Lianna F; Templeton, Megan; Fisher, Bridget; Lippy, Adriana; Jones, Chloe I; Lindestam Arlehamn, Cecilia S; Sette, Alessandro; Fuller, James T; Murapa, Patience; Jaspan, Heather B; Fuller, Deborah H; et al.
Abstract: BCG vaccination has been demonstrated to increase levels of activated CD4 + T cells, thus potentially influencing mother-to-child transmission of human immunodeficiency virus (HIV). To assess the risk of BCG vaccination in HIV infection, we randomly assigned newborn rhesus macaques to receive BCG vaccine or remain unvaccinated and then undergo oral simian immunodeficiency virus (SIV) challenges 3 weeks later. We observed elevated levels of activated peripheral CD4 + T cells (ie, HLA-DR + CD38 + CCR5 + CD4 + T cells) by week 3 after vaccination. BCG was also associated with an altered immune gene expression profile, as well as with monocyte activation in both peripheral blood and the draining axillary lymph node, indicating significant BCG vaccine–induced immune activation. Despite these effects, BCG vaccination did not increase the rate of SIV oral transmission or disease progression. Our findings therefore identify patterns of T-cell and monocyte activation that occur after BCG vaccination but do not support the hypothesis that BCG vaccination is a risk factor for postnatal HIV transmission or increased pathogenesis in infants. Abstract : BCG vaccination induces activation of CD4 + T cells, which potentially influences human immunodeficiency virus (HIV) infection in breastfeeding infants. This article demonstrates that BCG vaccine–associated T-cell and monocyte activation in infant macaques is not associated with oral simian immunodeficiency virus (SIV) transmission or pathogenesis.